Desorption kinetics of cesium from Fukushima soils. (March 2016) - Murota, Kento; Saito, Takumi; Tanaka, Satoru
Abstract: Understanding the behaviors of Cs + in soils is crucial for evaluation of the impacts of disposal of soils contaminated by radiocesium, 137 Cs. The desorption rate of Cs + evaluated in relatively short periods of time may not be adequate for such a purpose. In this study, we investigated long-term desorption kinetics of 137 Cs and 133 Cs from soils collected in Fukushima Prefecture by batch desorption experiments in the presence of cation exchange resin as a sorbent. The sorbent can keep the concentration of Cs + in the aqueous phase low and prevent re-sorption of desorbed Cs + . Up to 60% of 137 Cs was desorbed after 139 d in dilute KCl media, which was larger than the desorption by conventional short-term extraction with 1 M ammonium acetate. Desorption of 137 Cs continued even after this period. It was also found that high concentration of K + prevented desorption of Cs + in the initial stage of desorption, but the effect was alleviated with time. The desorbed fraction of stable Cs was smaller than that of 137 Cs. This indicated that 137 Cs may gradually move to more stable states in soils. The half-life of 137 Cs desorption from the slowest sorption site was estimated to be at least two years by a three-site desorption model. Graphical abstract: Highlights: Up to about 60% of 137 Cs was desorbed for 139 days in dilute KCl media. The fixation of Cs with high concentrations of K + was alleviated with time. The desorbed fraction of 133 Cs was much smaller than that of 137 Cs. Desorption of 137 Cs from the slowest sites was estimated to be in the order of years.